Psychological Conditions for Correction and Optimization of Personal Development of Adolescents with Depressive Disorders - Harkavenkо, Nina; Bihun, Nelia; Malyna, Olena; Doichyk, Maksym; Hoian, Ihor; Symonenko, Svitlana (BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 2021)
The article presents a theoretical generalization and a new solution to a scientific problem, expressed in the application of an innovative personal approach to solving the problem of adolescent depressive disorders, the basis of which is the scientific and methodological interpretation of personal development as a defining construct of the system of psychological conditions for the onset of depressive disorders, models of their diagnosis and psychological conditions for overcoming , which ensures the formation of adolescents' ability to effective personal self-regulation and an arbitrary choice of constructive ways of self-realization. The methodological foundations of the study of the personal properties of adolescents with depressive disorders are disclosed, a program for the diagnosis of personal symptoms of depressive disorders of various forms of severity in adolescent schoolchildren is presented; carried out a quantitative and qualitative analysis of the results of the ascertaining experiment on the psychological conditions of the onset of depressive disorders in adolescent schoolchildren and the personality traits of adolescents with depressive disorders; the description of personal phenomenology and symptomatology of depressive disorders in adolescents has been carried out. Theoretical substantiation of the formative experiment is given, the program of correction and optimization of personal development of teenagers as a means of overcoming their depressive disorders is presented, the quantitative and qualitative analysis of the results of its approbation is carried out. A profound restructuring of the structure and qualitative characteristics of the psychological conditions of the personal development of adolescents, their system of personal self-regulation, optimizes the functioning of the mechanism of personal sensitivity - "Ego" -tolerance to destructive influences, is, as the results of the application of the experimental correctional and developmental program, an effective way to overcome depression in adolescents’ disorders.
Keywords: personality development interpretation; personal self-regulation; constructive self-realisation ways; diagnostics of personal symptom